Design, synthesis, biological evaluation, structure-activity relationship, and toxicity of clinafloxacin-azole conjugates as novel antitubercular agents. Issue 1 (1st January 2019) - Liu, Jie; Ren, Zhenghong; Fan, Li; Wei, Jianyong; Tang, Xuemei; Xu, Xingran; Yang, Dacheng
Graphical abstract: Highlights: Clinafloxacin-azole conjugates were designed as novel anti-TB agents. Conjugates were tested against M. tuberculosis and indicator bacteria strains. TM2l exhibited good drug-likeness. Modifications to the 7-pyrrolidine amino group increased drug lipophilicity. Highly active anti-TB conjugates showed selectivity for M. tuberculosis . Abstract: Based on the advantages of azole molecules and fluoroquinolone drugs, we designed and synthesized 34 clinafloxacin-azole conjugates using fragment-based drug design and drug combination principles. The in vitro activities of the synthesized conjugates against Mycobacterium tuberculosis (H37Rv), Hela cell as well as Gram-positive and Gram-negative bacteria were assayed. The bio assay results revealed that most of the target molecules had anti-tuberculosis (anti-TB) activity, of which 14 compounds had very strong anti-TB activity [minimum inhibitory concentration (MIC) < 2 μM]. In addition, the compounds with strong activity towards H37Rv had weak activity towards Gram-negative and Gram-positive bacteria, showing obvious selectivity towards H37Rv. Predicted toxicity data indicated that 27 molecules were less toxic or equivalent to that of the original drug (clinafloxacin). Especially, it is demonstrated that compoundTM2l exhibited the strongest anti-TB activity (MIC = 0.29 μM), low antibacterial activity, negligible toxicity, and good drug-likeness values, which can be considered as an ideal lead molecule for future optimization.